PENGARUH SISTEM PEMUNGUTAN PAJAK, PELAYANAN FISKUS DAN EFEKTIFITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN LAYANAN DRIVE THRU SEBAGAI VARIABEL MODERATING - Nisa, Indah Chairun; Suwandi, Memen; Juardi, Muhammad Sapril Sardi (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
This study aims to examine the effect of tax collection system, tax service and tax system effectiveness on Taxpayer compliance with Drive Thru service. Taxes are dues that can be imposed without lead services or without direct rewards. Lack of compliance of the Taxpayer becomes the background of this research. This research is a quantitative research with associative approach. The data used in the study is the primary data collected through the division of questionnaires directly. Data analysis used multiple linear regression analysis and moderating regression analysis with Moderated Regression Analysis (MRA). The result of multiple linear regression analysis shows that tax collection system and fiscal service have a positive effect on taxpayer compliance. While the effectiveness of the tax system negatively affect the compliance of Taxpayers. Analysis of moderating variables with Moderated Regression Analysis (MRA) indicates that the Drive Thru service moderates the tax collection system and the effectiveness of the tax system on taxpayer compliance. But the fiscal services are not able to moderate the compliance of the Taxpayer.